The Meaning of Happiness in Islamic Philosophy: An Analysis of Mulla Sadra’s Thought on the Happiness of the Soul - Muhamad Basyr (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The concept of happiness is one of the important themes in Islamic philosophy tradition related to the ultimate goal of human life and spiritual perfection. In Islamic philosophy, happiness is not only understood as material pleasure or psychological condition, but as a spiritual state related to spiritual perfection and human closeness to God. This study aims to analyze the meaning of happiness in Islamic philosophy through an examination of Mulla Shadra's thoughts on the happiness of the soul. This study uses a qualitative approach with library research and a philosophical approach to examine conceptual ideas in the works of Mulla Shadra and related literature. The data sources consist of Mulla Shadra's major works as primary sources and books, scientific journal articles, and previous studies as secondary sources. Data analysis was conducted descriptively and analytically by interpreting the concept of spiritual happiness within the framework of hikmah al-muta'aliyah philosophy. spiritual perfection. The results of the study show that according to Mulla Shadra, true happiness is not only related to material aspects, but also to the perfection of the soul achieved through a process of self-purification, intellectual development, and spiritual closeness to God. Thus, happiness in Mulla Shadra's perspective is an existential condition achieved when the human soul reaches a level of perfection and harmony with metaphysical reality.